Empathy in Hippocampal Amnesia - Beadle, Janelle N.; Tranel, Daniel; Cohen, Neal J.; Duff, Melissa (Frontiers in Psychology, 2013)
The scientific investigation of empathy has become a cornerstone in the field of social cognition. Empathy is critical to the quality of our relationships with others and plays an important role in life satisfaction and well-being. Scientific investigations of empathy have focused on characterizing its cognitive and neural substrates, pointing to a network of brain regions involved in emotional experience and perspective taking (e.g., ventromedial prefrontal cortex, amygdala, anterior insula, cingulate). While the hippocampus has rarely been the focus of empathy research, we propose that there are compelling reasons to inquire about the contribution of the hippocampus to social cognition. We propose that the hallmark properties of the hippocampal declarative memory system (e.g., representational flexibility, relational binding, on-line processing capacity) make it well-suited to meet the demands of empathy. The present study is a preliminary investigation of the role of the hippocampal declarative memory system in empathy. Participants were three patients (1 female) with focal, bilateral hippocampal (HC) damage and severe declarative memory impairments and three healthy demographically matched comparison participants. Empathy was measured as a trait through a battery of gold standard questionnaires and through on-line ratings and prosocial behavior in response to a series of empathy inductions. Patients with hippocampal amnesia reported lower cognitive and emotional trait empathy than healthy comparison participants. In response to the empathy inductions, unlike healthy comparison participants, hippocampal patients reported no increase in empathy ratings or prosocial behavior from the control condition. Taken together, these results provide preliminary evidence for a role of hippocampal declarative memory in empathy.